The causal effect of schooling on smoking behavior. (October 2015) - Silles, Mary
Highlights: Explores the causal relationship between schooling and smoking. Compulsory schooling laws are used as instruments for schooling. The results for Great Britain indicate no causal role for education. For Northern Ireland schooling decreases smoking for men age 16 prior to 1962. Abstract: This paper, using data for Great Britain and Northern Ireland, examines the hypothesis that there is a causal relationship between schooling and cigarette smoking. Compulsory schooling laws are exploited to isolate for causation. Cohorts who were teenagers before and after the health consequences of smoking were widely known are used to compare the effects of additional schooling in the presence and absence of widespread exposure to health-related information. Although the results for Great Britain indicate no causal role for education either before or after the consequences of smoking for health were widely known, the results for Northern Ireland suggest that, at least among men, schooling affected smoking decisions prior to the public dissemination of knowledge on the dangers of smoking for health.